Slovakia: National Regulations in the Shadow of a Common Past - Ferenčíková, Simona (Criminal Legal Studies: European Challenges and Central European Responses in the Criminal Science of the 21st Century, 2022)
This chapter is devoted to the basics of substantive criminal law and criminal procedural law in Slovakia. Its aim is to define criminal law in the Slovak legal system and to specify the basic areas of its regulation. The chapter focuses on the criminal law itself, its development, and the subject of regulation. Within the scope of substantive criminal law, it focuses on the concept of criminal liability of natural and legal persons and on the system of criminal sanctions, including alternative sanctions. Within the framework of criminal procedural law, it focuses on criminal proceedings, their purpose, basic principles, stages, and alternative punishment in the form of diversions. It also addresses enforcement proceedings, in which it refers to the basic principles of enforcement. It pays special attention to the issue of the prison system. Finally, the legal acts of the European Union, which determined the wording of Slovak criminal law, are discussed. Finally, it evaluates the criminal legislation in the context of the state’s criminal policy. The Slovak Republic is known for the strictness of its criminal codes, which is reflected, in particular, in the definition of antisocial behavior and its subsequent designation as crimes for which the Slovak legal system, in comparison with other legal systems in Europe, imposes some of the most severe penalties.KEYWORDS: Slovakia, criminal law, criminal liability, criminal proceeding, criminal policy